Clinical Features and Treatment Outcomes of Children With Anaplastic Large Cell Lymphoma in Pakistan: A Multicenter Study. Issue 4 (May 2019) - Resham, Shahzadi; Khan, Rahil; Ashraf, Shamvil; Rizvi, Arjumand; Altaf, Sadaf
Abstract : Background: Different approaches have been adopted in the treatment of anaplastic large cell lymphoma (ALCL); there is a lack of consensus with regard to standard treatment. Because of paucity of data from low and middle-income countries, we reviewed the clinical features and treatment outcomes of children with ALCL. Methods: All ALCL patients under 16 years of age diagnosed from 2005 to 2015 at Aga Khan University Hospital and The Indus Hospital were identified. Clinical features and treatment outcomes were analyzed. Results: Thirty-two (n=32) patients met the inclusion criteria. Cervical Lymphadenopathy was the most common presentation (34.3%, n=11). Advanced disease was seen in 68.7% (n=22) (stages III and IV). Fourteen (42.4%) were treated on ALCL-99, 30.3% (n=10) on multicenter protocol-842 regimen, 9% (n=3) on adriamycin-prednisolone-oncovin (doxorubicin, prednisone, vincristine) regimen, and 16% (n=5) were treatment abandonments. Five-year overall survival was 70.6% (95% confidence interval: 47.8%-84.9%), and 5-year event-free survival (EFS) considering treatment abandonment and death as an event was 52.3 % (95% confidence interval: 23.5%-74.8%). Conclusions: Significant therapy-related mortality (27.7%) was observed. Treatment abandonment and therapy-related toxicity were the major barriers for better outcomes. However, less intensive outpatient regimens, such as adriamycin-prednisolone-oncovin regimen, may decrease the number of hospitalizations, hence reducing treatment abandonment in the low and middle-income country. Abstract : Supplemental Digital Content is available in the text.